POLA PERGERAKAN ANGKUTAN BARANG KABUPATEN KLATEN - herna pujiastutik (Retii, 2021)
Kabupaten Klaten is one of the regencies in Central Java Province which is flanked by two areas that have a fairly large traffic movement because it has a sand mining center located in Keimalang District and several industries factories in the Ceper and Kemudo areas. Where the factories are to transport their production goods into a mobilization system, a transportation system for the transportation of goods that is large enough to fulfill the mobility or industry. In determining the policy there are some data needed, such as traffic movement data. The data is used as material for analysis to formulate transportation policies in various regions in an effort to facilitate the demand for the movement of goods. These transportation policies are used to improve transportation equipment as a form of intervention from the supply side on the road network. Because there is no recapitulation of the movement of goods transport in the Kabupaten Klaten as a tool for determining policies by the local government in determining several policies, it is necessary to analyze the movement of goods transport traffic in Kabupaten Klaten. Methods This research uses descriptive quantitative research methods with Secondary Data Analysis (ADS) approach. ADS is a method by utilizes secondary data as the main data source. Utilizing secondary data in question, namely by using an appropriate statistical test to obtain the desired information from the material body or from mature data obtained from certain Agencies or Institutions (such as BPS, Departments or Educational Institutions) to be processed systematically and objectively. . The secondary data used in this study is survey data that has been carried out by the Ministry of Transportation, Transportation Research and Development Agency, Survey of Origin and Destination of Goods Transportation in 2018. The volume of movement of goods transport from Klaten Regency to Regencies in Central Java Province is 589,411 tons/month and from Regencies in Central Java to Klaten Regency is 520.554 tons/month. The pattern of the movement of goods transportation to Klaten Regency from Regencies in Central Java is the largest to Sragen, Boyolali, Wonogiri, Sukoharjo, and followed by other Regencies. For the pattern of movement of goods transportation from Klaten Regency to Central Java, the largest districts are Sukoharjo, Boyolali, Magelang, and Surakarta and followed by other districts Keywords: Freight Transportation, Kabupaten Klaten, Movement Pattern